2022
DOI: 10.3389/fimmu.2022.911546
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T Helper 22 Cells in Dermatological Disorders

Abstract: T helper 22 (Th22) cells are a newly identified subset of CD4+ T cells that secrete the effector cytokine interleukin 22 (IL-22) upon specific antigen stimulation, barely with IFN-γ or IL-17. Increasing studies have demonstrated that Th22 cells and IL-22 play essential roles in skin barrier defense and skin disease pathogenesis since the IL-22 receptor is widely expressed in the skin, especially in keratinocytes. Herein, we reviewed the characterization, differentiation, and biological activities of Th22 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 258 publications
(369 reference statements)
0
8
0
Order By: Relevance
“…The main secretion of Th22 is IL-22 [ 30 ]. Moreover, studies have shown that IL-22 can promote the proliferation of keratinocytes, inhibit their differentiation, promote the expression of related keratin, control hair follicle circulation, and promote hair growth [ 31 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main secretion of Th22 is IL-22 [ 30 ]. Moreover, studies have shown that IL-22 can promote the proliferation of keratinocytes, inhibit their differentiation, promote the expression of related keratin, control hair follicle circulation, and promote hair growth [ 31 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Significantly higher amounts of IL-22-producing T cells are distinct in AD patients [ 30 ]. Keratinocytes express IL-22 receptors widely, and studies have shown that IL-22-keratinocyte crosstalk plays an essential role in skin barrier defense and AD pathogenesis [ 31 ]. Real-time PCR data revealed that the most prominent gene activation of Th22 immune pathways was found in skin samples of the acute phase and then progressively increased during the chronic phase of the disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…S100A proteins have proinflammatory functions, including chemotaxis of T‐cells 21 . Although S100A8 , S100A9 , and S100A12 expression is induced by both Th22 cytokine (IL‐22) and Th17 cytokine (IL‐17) signaling in AD skin, 22,23 IL‐22 acts via JAK1 signaling, whereas IL‐17 does not (Figure S5). 1,11 Therefore, abrocitinib, a JAK1 inhibitor, likely reduced S100A8 , S100A9 , and S100A12 expression by inhibiting IL‐22 signaling.…”
Section: Discussionmentioning
confidence: 99%